A study of functional selectivity at the cannabinoid type 1 receptor - Priestley, Richard (2015)
The cannabinoid CB1 receptor is a G protein-coupled receptor (GPCR) which is important in the regulation of neuronal function, predominately via coupling to heterotrimeric Gi/o proteins. The receptor has also been shown to interact with a variety of other intracellular signalling mediators, including other G proteins, several members of the mitogen activated kinase (MAP) superfamily and β-arrestins. The CB1 receptor is recognised by an array of structurally distinct endogenous and exogenous ligands and a growing body of evidence indicates that ligands acting at GPCRs are able to differently activate specific signalling pathways, a phenomenon known as functional selectivity or biased agonism. This is important in future drug development as it may be possible to produce drugs which selectively activate signalling pathways linked to therapeutic benefits, while minimising activation of those associated with unwanted side effects. The main aim of this thesis, therefore, was to investigate ligand-selective functional selectivity at the cannabinoid CB1 receptor both endogenously and exogenously expressed in a variety of cell lines.